Combined Oxytocin and Cognitive Behavioral Social Skills Training for Social Function in People With Schizophrenia. Issue 3 (23rd May 2021) - Buchanan, Robert W.; Kelly, Deanna L.; Strauss, Gregory P.; Gold, James M.; Weiner, Elaine; Zaranski, Jennifer; Chen, Shuo; Blatt, Frank; Holden, Jason; Granholm, Eric
Abstract : Supplemental digital content is available in the text. Abstract: Background: A significant proportion of people with schizophrenia are characterized by impaired ability to socially engage with others. The development of effective interventions for social functioning remains a central therapeutic challenge. Cognitive-behavioral social skills training (CBSST) has been found to improve social functioning in schizophrenia, but with only medium effect sizes. Intranasal oxytocin also has prosocial effects, but also only with modest effect sizes. This study assessed whether the addition of intranasal oxytocin to CBSST can strengthen their impact on social function. Methods: Participants (N = 62) with schizophrenia or schizoaffective disorder entered a 24-week, double-blind, placebo-controlled, randomized clinical trial with a 3-month follow-up evaluation at 2 sites: Maryland and San Diego. Participants were randomized to either intranasal oxytocin 36 IU (3 sprays) twice a day (n = 31) or intranasal placebo-oxytocin (3 sprays) twice a day (n = 31). All participants received CBSST plus a social cognition skills training module (48 total sessions). Results: There were no significant treatment group differences in social functioning, positive symptoms, negative symptoms, defeatist beliefs, or asocial beliefs. The interpretation of treatment effects was complicated by site effects, whereby participants in San Diego began the trial with greater severity of impairments and subsequently showed greater improvements compared with participants in Maryland. Conclusions: The results did not support the utility of add-on intranasal oxytocin to psychosocial rehabilitation interventions like CBSST for improvement in social function (ClinicalTrials.gov trial number: NCT01752712).